Παραγωγή υποκατάστατου φυσικού αερίου και Μεθανόλης για αποθήκευση ενέργειας - Κουτσούμπα, Ευθυμία Ιωάννα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Θερμότητας. Εργαστήριο Ατμοκινητήρων και Λεβήτων, 2017)
The scope of the thesis with the title “Production of Substitute Natural Gas and Methanol for energy storage” is the process design and techno-economic evaluation of power to fuel technologies. The present thesis is divided in 6 chapters. Chapter 1 presents the motivation and structure of the thesis. The European Union (EU) energy strategy for 2030 and 2050 sets specific targets for the transition of the current European energy system towards a low carbon energy system with increased energy efficiency, increased share of Renewables Energy Sources (RES) and renewable transport fuels. The present thesis is focusing on future scenarios for the energy mix, where RES penetration is more than 27%, and the otherwise curtailed RES electricity is used as a mean for energy storage for the production of methanol as substitute for transportation fuels and other chemical derivatives and Substitute Natural Gas (SNG) as substitute for fossil natural gas. Power to Fuel concept involves the use of electrolysers, which are operated during surplus electricity hours of RES overproduction in order to split water to oxygen and hydrogen. The latter is subsequently used together with otherwise emitted CO2 to produce methane and methanol integrated in a landfill plant and in a biomass and lignite fired power plant in the framework of this thesis. The combination of water electrolysis and solid fuel gasification offers the substitution of Air Separation Unit, the reduction or elimination of water gas shift catalytic system and acid gas removal technology. Subsequently, the direct utilisation of CO2, which otherwise would be emitted in the production process and its conversion to valuable fuels in combination with energy storage is achieved. The combination of biomass gasification and power to fuel technology is investigated towards renewable fuel production. Moreover, the use of lignite and RES derived electricity is investigated for the production of fossil derived methanol and SNG in combination with energy storage and reduction of energy imports. Chapter 2 focuses on the SNG and methanol production via catalytic processes. Equilibrium simulations via modelling in AspenPlus are performed in various process conditions for pure mixtures of H2, CO and CO2 in order to define the optimum conditions for maximum conversion in isothermal and adiabatic reactors. In addition, kinetic approach for the CO2 derived methanation and methanol is modelled and compared with the equilibrium results. Chapter 3 is investigating the implementation of power to SNG and power to methanol as means of energy storage and CO2 utilisation in three different cases, namely a landfill plant, a biomass and a lignite fired power plant. The state of the art electrolyser and CO2 capture technology is reviewed. MDEA is modelled in AspenPlusTM for pre and post combustion capture and optimised via using low temperature heat and reducing the imported steam. Catalytic SNG synthesis is modelled in AspenPlusTM and optimised according to the power to fuel technology and gas specifications. Methanol and distillation synthesis are modelled with equilibrium approach. The cold fuel efficiency of power to SNG ranges between 51.59% to 52.25%, while for the power to methanol between 53.26% to 54.17%. The overall process integration of power to SNG resulted in an energy conversion efficiency of 78.72% for the landfill case, where hot flue gases from an internal combustion engine are used, and 52.55% and 52.66% for the biomass and lignite fired plant respectively. The overall process integration of power to methanol resulted in an energy conversion efficiency of 71.89% for the landfill case, where hot flue gases from an internal combustion engine are used, and 52.28% for both the biomass and lignite fired power plant case. Chapter 4 accesses steam, oxygen and mixture of steam and oxygen gasification for methanol and SNG production with a combination of electrolysers in two different scales with the aim to define the optimum efficiencies and to reduce the direct CO2 emissions during the productionprocess. Modelling of steam and steam/oxygen gasification process is performed in AspenPlusTM according to a correlated gasification model with experimental values for sunflower from an atmospheric fluidised bed gasifier. The gas cleaning and conditioning technologies required for the syngas produced via the gasification focusing on activated carbon, water gas shift, tar reforming and acid gas removal technologies are investigated. Gas cleaning and scavenging is experimentally investigated in terms of activated carbon s capacity for the removal of toluene, naphthalene and hydrogen sulphide, carbonyl sulphide and carbon disulphide. Chemical solvents are investigated with equilibrium approaches using potassium carbonate and MDEA. Capture ratios are balanced with and without water gas shift reactor according to the requirements of the fuel synthesis. The cold fuel efficiency of gasification and power to SNG ranges between 57.67% to 63.43% for the optimum cases with low pressure steam/oxygen gasification and electrolysers sized according to oxygen demand and according to the oversized electrolysers case respectively. The respective overall process efficiency for the SNG cases resulted in an energy conversion efficiency of 72.83% and 73.51% with the production of steam. The cold fuel efficiency of gasification and power to methanol was equal to 53.20% to 53.70% for the optimum cases with high pressure steam/oxygen gasification and electrolysers sized according to oxygen demand and according to the oversized electrolysers case respectively. The respective overall process efficiency for the methanol cases after use of the purge stream resulted in an energy conversion efficiency of 59.19% and 58.71% with the production of steam. Chapter 5 includes a sensitivity analysis of process parameters and their influence on the final energy efficiency for the cases of power to fuel and for the combined gasification and power to fuel process. A techno-economic analysis of the two concepts is presented and the optimum conditions, under which an investment on these technologies would be viable are investigated. Methanol production via power to fuel is advantageous in all cases studied compared to the combined gasification and power to fuel technology due to lower capex. For the lignite case, where no premium prices are applied, the gasification and power to fuel technology could be applied in scales of 100MWth of methanol under specific conditions. For the SNG cases studied, it was found that high subsidies are required to make such an investment viable and among the cases studied, power to SNG is a preferable option only if the electricity price is lower than 20 EUR/MWh. It is concluded that from the techno-economic point of view methanol production presents better business cases than SNG production. The marginal/premium prices for the viability of the investment for the two fuels are also investigated Chapter 6 presents the conclusions of the phd thesis and suggestions for future work.